Development of Multimedia-Based Mobile Learning in Class X SMKN Informatics Subjects - Hariadi, Syarif Novalin; Hendri, Nofri; Hidayati, Abna; Zuliarni, Zuliarni (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research discusses the development of multimedia-based mobile learning in class X informatics subjects of SMKN. The purpose of the research is to develop a mobile learning product based on multimedia in class X informatics subjects at SMKN. This research method is development research (R&D) with a 4D development model. The population in this study was all grade X students at SMKN 1 West Pasaman. The sample of this study amounted to 25 respondents taken from one class X at SMKN. The data collection tool used a questionnaire with a total of 19 question items. The data analysis technique used is descriptive quacitivative, using Likert scale. The results of research on learning media development by media validators 1 and 2 were obtained